Magnetic Ni-Co alloy encapsulated N-doped carbon nanotubes for catalytic membrane degradation of emerging contaminants - Kang, J.; Zhang, H.; Duan, Xiaoguang; Sun, Hongqi; Tan, X.; Liu, Shaomin; Wang, Shaobin (Elsevier BV, 2019)
Nitrogen-doped carbon nanotubes encapsulated with Ni-Co alloy nanoparticles (NiCo@NCNTs) were readily synthesized by annealing Ni/Co salts with dicyandiamide. The magnetic nanocarbons were assembled as a flat membrane for heterogeneous degradation of organic toxins. The synergistic effect of nitrogen doping and metal alloy encapsulation significantly enhanced the catalytic activity and stability of NCNTs in catalytic activation of peroxymonosulfate (PMS) for purification of an emerging pollutant, ibuprofen. The hybrid catalyst yielded a fast reaction rate of 0.31 min-1, which was 23.4 and 5.8 times higher than that of pristine CNTs and monometallic (Ni or Co) encased CNTs, respectively. The robust membrane catalysis was further confirmed by degrading other organic aqueous pollutants, such as naproxen, sulfachloropyridazine, phenol, methylene blue, and methyl orange. Mechanistic investigation was performed using electron paramagnetic resonance and competitive radical screening tests, which indicated that radical ([rad]OH and SO4[rad]-) oxidation and nonradical pathway co-existed and played critical roles for catalytic degradation. The study provides a novel advanced oxidation system with catalytic membrane for wastewater remediation.